(3GdLGeY dCNdGb GdQGhis - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s
(3ChdgG (B:s
(3CeG HYO abO PcQJ ai cJGH TQa GUMGH GdMOjK eG jLOhG CKGQ QShd Gddg Udi Gddg Ydjg hSde hGdELJgGO ai WdHgG hGdMQU Ydi SeGYgG s
(3BNQgG (B:s
(3bGd QLd cGf jYed ai TjHJg NjQkG acHQ hYLd Yf Pdc agh jLQi Ydjg ef GdGLQ eG cGf jLQi Ydjg ai THjJg hUMJg dGjef Ydjg HPdc gPG BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG SeGY dCHi GdMSf SYO GdNjQ Hf eMeO Hf Sgd GdGfUGQi hHfGJg Ydi GdTjN CHj GdbGSe GdTgQRhQi HMb GLGRJg Yf GdeUfa ai SfI (B529(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs